Overview of Replication Techniques on Distributed Database in Cloud Environment - Sharifah Hafizah, Syed Ahmad Ubaidillah; Noraziah, Ahmad (American Scientific Publishers, 2017)
Replication is a topic of interest in the cloud computing, distributed systems, and database communities. It is also one of the practical methods in distributed systems for developing better reliability and availability. Replication is employed to reduce user waiting time, increasing data availability and decreasing cloud system bandwidth used by offering the user numerous replicas of a detailed service on multiple nodes in cloud computing. This paper presents an overview of replication techniques on distributed database in the cloud environment.